An investigation on the application and challenges for wide area monitoring and control in smart grid - Marwan Ahmed Abdullah Sufyan; Mohd Zuhaib; Mohd Rihan (Bulletin of Electrical Engineering and Informatics, 2021)
The complexity and dynamics of the modern power system are continuously changing due to the penetration of a large number of renewable energy sources and changing load patterns. These growing complexities have caused numerous outages around the world, primarily due to the lack of situational awareness about the grid operating states. Rectification of this problem requires advanced sensing technology to accurately capture the dynamics of the system for better monitoring and control. Measurement of synchrophasors is a potential solution to improve situational awareness in the grid. The synchrophasors technology is now widely accepted throughout the world and has the potential to replace the existing SCADA system in monitoring and control of the power system. Their installation enables efficient resolution to substantially improve transmission system planning, maintenance, operation, and energy trading. This paper reviews the state of the art potential applications that the PMU based WAMC offers to the power system. It also includes technical perspectives, challenges, and future possibilities.